2018
DOI: 10.1371/journal.pone.0206635
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure and noncommunicable diseases in middle-aged and older adults in China

Abstract: BackgroundThere are few studies examining the association between blood pressure (BP) and noncommunicable diseases (NCDs) in consideration of the new hypertension guidelines in China.MethodsData were drawn from the China Health and Retirement Longitudinal Study. 14 390 eligible participants (aged 45 years and older) were selected through four-stage, stratified, and cluster sampling. Hypertension was considered as a mean systolic blood pressure (SBP) of 130 mm Hg (old definition: 140 mm Hg) or higher, a mean di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…The presence of non-communicable diseases other than hypertension was found to be a significant risk factor for hypertension, consistent with previous studies. 26 Being overweight or obese was significantly associated with hypertension risk, which is in line with numerous studies. 18,19,21,27,28 This highlights the importance of weight management and healthy lifestyle interventions in preventing and managing hypertension.…”
Section: Discussionsupporting
confidence: 88%
“…The presence of non-communicable diseases other than hypertension was found to be a significant risk factor for hypertension, consistent with previous studies. 26 Being overweight or obese was significantly associated with hypertension risk, which is in line with numerous studies. 18,19,21,27,28 This highlights the importance of weight management and healthy lifestyle interventions in preventing and managing hypertension.…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, high blood pressure occurred as a highly scored feature in the population of the United States. Similarly, a study [60] found an eminent association between high blood pressure and NCDs among middle-aged and older adults (aged 45 years and older) in China. In addition, approximately 9.4 million deaths are estimated caused by raised blood pressure, which means approximately 40% of adults have hypertension [61].…”
Section: Global and Local Explanation Resultsmentioning
confidence: 85%
“…1 Hipertensi dapat dicegah dengan berhenti merokok, memenuhi kebutuhan air dalam tubuh, melakukan aktivitas fisik secara rutin, menjaga pola istirahat, dan menghindari terjadinya stress. 7 Sedangkan penatalaksanaan hipertensi adalah meminum obat antihipertensi dan modifikasi gaya hidup. Efektivitas obat antihipertensi dinilai baik, namun kepatuhan terhadap rejimen pengobatan seringkali buruk.…”
Section: Pendahuluanunclassified